Nuts, anchor, self-locking, floating, two lug, with incremental counterbore, with MJ threads, classifications: 900 MPa (at ambient temperature)/235°C, 900 MPa (at ambient temperature)/315°C and 900 MPa (at ambient temperature)/425°C. Dimensions. (15th April 1999) - British Standards Institution,
No abstract available